(untitled) (Research, Society and Development, 2022)
Anteaters comprise three different species: Myrmecophaga tridactyla (flag anteater), Tamandua tetradactyla (mini anteater) and Cyclopes didactylus (anteater), some considered vulnerable to extinction. These species are distributed over a large part of the Brazilian territory, especially in the cerrado biome. In order to preserve these species, some research work on the health status of these animals has been carried out, both in captive and free-living animals. The objective of this study was to investigate keratinophilic filamentous fungi, including dermatophytes, in the coat of 27 adult anteaters retained in captivity. Among the animals studied, 14 were giant anteater (Myrmecophaga tridactyla) and 13 were small anteater (Tamandua tetradactyla). These specimens were retained at the São Paulo Zoological Park Foundation and Quinzinho de Barros Municipal Zoological Park. Samples were obtained by means of rubbing sterilized squares of carpet on the coat of each animal. Each carpet was seeded in Petri dishes containing Mycobiotic™ agar medium (Difco™) and incubated at 25ºC until colony growth was observed. Dermatophytes were not isolated; however, the following genera of filamentous fungi were identified: Cladosporium spp. (51.8%), Scopulariopsis sp (29.6%), Aspergillus spp. (22.2%), Acremonium spp. and Chrysosporium spp. (11.1%) and Mucor spp. (7.4%), among these we highlight the keratinophilics: Scopulariopsis sp, Acremonium spp. and Chrysosporium spp. There are few studies on the prevalence of dermatophytes and other keratinophilics in wild animals and none on anteaters. It was possible to confirm the presence of non-dermatophytic keratinophilics in the normal microbiota of anteaters, similarly to what was observed in other mammals.